Unusual fusion gene rearrangements in patients with nodular fasciitis: a study of rare and novel USP6 fusion partners with a review of the literature - Balko, Jan; Stanek, Martin; Krskova, Lenka; Zamecnik, Josef (Journal of clinical pathology, 2024)
AIMS: This retrospective non-randomised study aims to identify new and rare fusion partners with USP6 in the setting of nodular fasciitis. It has been proven, that nodular fasciitis can harbour different variants of USP6 fusions, which can be used in routine diagnostics and even determine the biological behaviour of the process. METHODS: A total of 19 cases of nodular fasciitis examined between 2011 and 2022 at Motol University Hospital in Prague were included into this study. Next to the histopathological evaluation, all cases were assessed using immunohistochemistry, RT-PCR and Anchored multiplex RNA methods. Patient's main demographic characteristics and corresponding clinical data were also analysed. RESULTS: This study presents one novel (KIF1A) and five rare examples (TMP4, SPARC, EIF5A, MIR22HG, COL1A2) of fusion partners with USP6 among 19 cases of nodular fasciitis. CONCLUSION: Identification of USP6 fusion partners in nodular fasciitis helps to understand the biology of such lesions. Moreover, it can be useful in routine histopathological practice of soft-tissues diagnostics, especially in preventing possible misdiagnosis of malignancy.
Keywords: dospělí; Female; Adult; ženské pohlaví; mladý dospělý; genová přestavba; fúzní onkogenní proteiny; Immunohistochemistry; lidé; Ubiquitin Thiolesterase; Oncogene Proteins, Fusion; thiolesterasa ubikvitinu; imunohistochemie; Fasciitis; retrospektivní studie; Male; fasciitida; Aged; Young Adult; Gene Rearrangement; lidé středního věku; Kinesins; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; kineziny; Humans